Oscillatory and asymptotic behaviour of a neutral differential equation with oscillating coefficients - Julio Dix; N. Misra; Laxmi Padhy; Radhanath Rath (Electronic Journal of Qualitative Theory of Differential Equations, 2008)
In this paper, we obtain sufficient conditions so that every solution of $$ \big(y(t)- \sum_{i=1}^n p_i(t) y(δ_i(t))\big)'+\sum_{i=1}^m q_i(t) y(σ_i(t)) = f(t) $$ oscillates or tends to zero as $t → ∞$. Here the coefficients $p_i(t), q_i(t)$ and the forcing term $f(t)$ are allowed to oscillate; such oscillation condition in all coefficients is very rare in the literature. Furthermore, this paper provides an answer to the open problem 2.8.3 in [7, p. 57]. Suitable examples are included to illustrate our results.